Hidden in plain sight: the identity of the white-leaved snakewood species from southeastern Brazil, Cecropia candida Snethl. and Cecropia hololeuca Miq. (Urticaceae) - Da Silva, Marcus Felippe Oliveira; Dos Santos Maia, Vitor Hugo; de Freitas Mansano, Vidal (Phytotaxa, 2019)
The identity of Cecropia candida, a misidentified snakewood species from Brazil, are also discussed. Its relationships to Cecropia hololeuca, another white-leaved species from Brazil, are also discuted.